Predicting Future Trend of Customers in Banking Sectors in India using Mathematical Modeling - Neetu Rani, Deepak Garg; Savita Garg (International journal of economic perspectives, 2017)
A mathematical model for determining customers’ population in various banking sectors in India has been developed with the aid of compartmental diagrams. For deriving this model, the concept of rate of change has been used. The model emerges in the form of differential equations which have been solved with the help of linear algebra technique. A solution of these differential equations has been shown graphically using the mathematical software Mathematica, so that the solution can be visualized and understood by anyone having no higher mathematical background. Numerical discussion has been carried out for hypothetical data taken as per observed trend of customers in various banking sectors in the current scenario. The present study shows that private and foreign banks dominate the public sector and cooperative banks in context of number of customers dealing. Private and foreign banks show continuous progress in attracting customers whereas public sector and cooperative banks take half of the time span of 100 years to show positive performance and to create confidence of the customers. The scope of future research has also been proposed in terms of finding the possible non-zero solutions of homogenous system of linear equations resulting in evaluation of equilibrium points lying in number of customers of various banking sectors.